40/#906 The diagnostic accuracy of colposcopy for cervical intraepithelial neoplasia 2+ among HIV positive and negative South African women. (4th December 2022) - Visser, Cathy; Dreyer, Greta; Botha, Matthys; Snyman, Leon; Merwe, Frederick Van Der; Richter, Karin; Breytenbach, Erika; Dreyer, Gerrit J
Abstract : Objectives: We evaluated performance of Reid's Colposcopic Index (RCI) versus colposcopic impression (CI) to diagnose histologically confirmed CIN2+ lesions. Methods: RCI was calculated as negative(RCI 0–2), low-grade(RCI 3–4), high-grade(RCI 5+); CI was logged as negative, low-grade/uncertain or high-grade. Directed punch biopsy (suspicious lesions) or blind punch biopsies (negative lesions) were taken. Worst of biopsy or treatment result was regarded as final histological diagnosis. Results: Included were 725 participants; mean age 40.7 years; 46.8%(339/725) were HIV positive and 53.2%(386/725) HIV negative. In HIV positive and -negative groups, RCI was high-grade in 35.1%(119/339) and 11.1%(43/386)(p<0.0001) respectively; CI was high-grade in 30.1%(102/339) and 9.1%(35/386)(p<0.0001) respectively. Histology confirmed CIN2+ in 49.9%(169/339) HIV positive and in 29.5%(114/386) HIV negative women (p<0.0001). CIN3+ diagnosed in 26.8%(91/339) HIV positive and 13.0%(50/386) HIV negative participants. For RCI to predict CIN2+ in the HIV positive cohort, sensitivity, specificity, PPV and NPV were 80.6%, 56.9%, 64.6% and 75.0%, and for CI 82.4%, 56.3%, 61.8% and 76.6% respectively. For RCI in the HIV negative cohort these figures were 63.0%, 72.4%, 49.0% and 82.3%, and for CI 63.9%, 70.2%, 47.5% and 82.2% respectively. Conclusions: Colposcopy test performance differs significantly between HIV positive and -negative cohorts. Validity of colposcopy in HIV positive women to identify possible CIN2 for biopsy is confirmed. Among HIV negative women sensitivity of colposcopy is relatively low and blind biopsies are warranted. RCI and CI performed equally in both HIV positive and negative cohorts. In this study, using the RCI scoring system did not contribute significantly to the accuracy to predict pre-invasive lesions.